A Case of Postoperative Recurrent Lumbar Disc Herniation Conservatively Treated with Novel Intradiscal Condoliase Injection - Toru Funayama; Yusuke Setojima; Yosuke Shibao; Hiroshi Noguchi; Kousei Miura; Fumihiko Eto; Kosuke Sato; Mamoru Kono; Tomoyuki Asada; Hiroshi Takahashi; Masaki Tatsumura; Masao Koda; et al. (Case Reports in Orthopedics)
Although postoperative recurrent lumbar disc herniation (rec-LDH) is uncommon, it is a challenging situation that requires revision surgery when conservative treatment fails. Recently, an agent inducing chemical dissolution of the nucleus pulposus using condoliase has been approved as a novel intradiscal treatment for LDH. To date, no evidence has been reported regarding its effectiveness in the treatment of postoperative rec-LDH. A 25-year-old man with a history of LDH in L4/5, who underwent transforaminal full endoscopic lumbar discectomy when he was 17 years old, complained of severe pain radiating to his left leg since 1 month. The straight leg-raising test was limited to 25° on the left side. Lumbar T2-weighted magnetic resonance imaging (MRI) showed intracanal, left-sided transligamentous disc herniation at L4/5 with high-signal intensity. Because the conservative treatment with oral analgesics and selective left L5 nerve root block failed, the patient requested intradiscal condoliase injection instead of revision surgery. There were no adverse events reported after the condoliase treatment, and the pain radiating to the left leg improved within 2 weeks. A lumbar MRI performed 2 months after treatment revealed that the disc herniation had significantly decreased in size. The straight leg-raising test examined 3 months after treatment was negative. In this case, the disc herniation was of the transligamentous type and showed a high-signal intensity on T2-weighted MRI which could be suitably treated by condoliase injection therapy. This case report is the first to suggest that intradiscal condoliase injection could be a useful and novel conservative treatment option to treat postoperative rec-LDH.